Motivasi Kerja Pada Karyawan Kontrak di Indonesia: Literature Review - Bayu Kurniawan; Fatkhur Risqi; Riyan Sisiawan Putra; Alifiya Anggraini; Vanca Lova (CV. Ulil Albab Corp, 2022)
This paper examines the work motivation of contract employees and the topic is limited because it only occurs in Indonesia. Then, there are not many studies that discuss work motivation for contract employees. Therefore, this literature study aims to discuss further about several studies related to work motivation in contract employees. Literature search was carried out on the Google database and specifically on a collection of University journals in Jakarta from 2019 to the present, there are 3 research journal articles that have been identified using inclusive and exclusive criteria, based on reviews that have been carried out, including the contract work system carried out according to with an agreement that has been signed together, it will improve employee performance by paying attention to and properly implementing work agreements, provisions regarding the period of service and providing employee wages in accordance with the provisions. High work motivation will have a positive impact on improving the performance of Contract employees by increasing love for the work given, cooperation, responsibility and enthusiasm for work